A comprehensive appraisal of mechanism of anti-CRISPR proteins: an advanced genome editor to amend the CRISPR gene editing - Choudhary, Nisha; Tandi, Dipty; Verma, Rakesh Kumar; Yadav, Virendra Kumar; Dhingra, Naveen; Ghosh, Tathagata; Choudhary, Mahima; Gaur, Rajarshi K.; Abdellatif, Magda H.; Gacem, Amel; Eltayeb, Lienda Bashier; Alqahtani, Mohammed S.; et al. (Frontiers in Plant Science, 2023)
The development of extremely controlled and precise CRISPR-Cas tools has been made possible by the discovery of protein inhibitors of CRISPR-Cas systems, called anti-CRISPRs (Acrs). The Anti-CRISPR protein has the ability to control off-targeted mutations as well as impede Cas protein editing operations. Anti-CRISPR can help with selective breeding, which could help plants and animals improve their valuable features. In this review, the anti-CRISPR protein-based inhibitory mechanisms that have been adopted by several Acrs, such as (a) the interruption of CRISPR-Cas complex assembly, (b) interference with target DNA binding, (c) blocking of target DNA/RNA cleavage, and (d) enzymatic modification or degradation of signalling molecules, were discussed. In addition, this review emphasises the applications of anti-CRISPR proteins in therapeutics and plant research.